Social measures to prevent criminal offenses against the environment: a historical and critical analysis in Ukraine from 1991 to present - Marko Serhiy; Yuliia Borutska; Oleksandr Voroniatnikov; Daria Kiblyk (Clío, 2025)
The general objective of the research consists, on the one hand, in analyzing, from a critical and historical perspective, the legal framework that typifies the crimes committed against the environment in Ukraine, in a chronological period of 34 years, from 1991 to the present. On the other hand, social measures to prevent the commission of these crimes are discussed. Methodologically, it is a work developed because of the parameters of the historical method, with a predominance of documentary sources, such as: official documents, laws, press releases and scientific articles of high impact. The results obtained allow us to conclude that, beyond the romantic ecological discourses, the imperative need to defend the environment in the 21st century is becoming increasingly critical in view of the imminent risk of the collapse of human civilization due to poor management of natural resources.